Early struggles - the relationship of psychopathology and development in early childhood - Martin, Annick; Galeris, Mirijam-Griseldis; Theil, Mona K.; Sele, Silvano; Cavelti, Marialuisa; Keil, Jan; Kaess, Michael; von Polier, Georg G.; Schlensog-Schuster, Franziska (Children, 2025)
BACKGROUND/OBJECTIVES: Early childhood psychopathology has a profoundly negative impact on various areas of psychosocial functioning. Psychopathology and child development are closely linked and influenced by a range of factors, such as socioeconomic status and pre- and postnatal risks. This cross-sectional study aims to gain a deeper understanding of child development in children with early psychopathology and to derive implications for the diagnosis and treatment of the youngest children. - METHODS: This cross-sectional study examines the developmental status of children aged 0 to 5 years with early psychopathology (EPP) in comparison to gender- and age-matched healthy controls (HC). A newly self-developed objective, semi-structured, symptom-based interview was administered in each subgroup by trained research assistants. This interview is based on the DC: 0-5 classification system. The ET 6-6-R was used as a standardized developmental test, covering the developmental areas of gross and fine motor skills, cognition, language development, and socioemotional development. Demographic characteristics, including maternal education and household income, were considered as potential confounders. - RESULTS: Children with early pathology elicited a lower total developmental quotient than healthy controls. HC demonstrated a better performance in fine motor skills, language development, and socioemotional development than their counterparts with EPP. HC showed better gross motor skills as well, but statistical significance was p = 0.08. After controlling for maternal education, overall development and socioemotional development were found to be lower in the EPP group than in the HC group. - CONCLUSIONS: These findings highlight the need to identify psychopathology and associated developmental deficits early in childhood which might allow more targeted treatments, enhancing developmental opportunities for affected children.